FORMATION OF VALEOLOGICAL CULTURE IN PRIMARY SCHOOL PUPILS - Uralova Gulbahor Oktamovna (EPRA International Journal of Research and Development (IJRD), 2022)
In this article, it is stated that human health, well-being of the population, the growth of a harmoniously developed generation and the development of society are important tasks, and also opinions and comments on the role of valeology in the high productivity of the intended purpose are stated to achieve efficiency and to start this process from children of primary school age.